Pedagogia da tradução baseada em corpus: Associações entre teorias e práticas do ensino do habitus tradutório por meio de corpora - Serpa, Talita [UNESP]; Rocha, Celso Fernando [UNESP] (Universidade Estadual de Maringa, 2016)
The concept of habitus (Bourdieu, 1980) represents an experience system that works as a matrix of actions and makes possible to perform tasks. By applying this conception in Translation Studies, authors such as Simeoni (1998) suggest the existence of a translational habitus, which contributes to the formulation of translation strategies. As part of the Pedagogy related to translation, Díaz Fouces (1999) states that there is a guideline devoted to teaching, which is directed to the recognition of real language use via corpora, so that it can facilitate the systematization of information to serve as a basis for practice. Therefore, our theoretical approach is based on Corpus Linguistics (Berber Sardinha, 2010), Corpus Based Translation Studies (Baker, 1996, 2000) and Corpus Based Translation Pedagogy (Laviosa, 2009; Camargo, 2011). We prepared a proposal for teaching and we organized a corpus composed by the work called Maíra (Ribeiro, 1976) and by its respective translation. We also undertook a reflection on teaching how to translate terms (Barros, 2004) and brazilianisms (Faulstich, 2004), as well as conducted an exercise in translation practice in which students were confronted with a possible assimilation of application of translational habitus.
Corpus based translation pedagogy: Theory and practice for teaching translational habitus using corpora
Keywords: Brazilianisms; Corpus based translation pedagogy; Corpus based translation studies; Corpus linguistics; Translational habitus